RP-HPLC Method for the Determination of Cinitapride in the Presence of its Degradation Products in Bulk Drug - S. M. N. Roy; Kiran V. Mangaonkar; A. Y. Desai; Santosh M. Yetal (E-Journal of Chemistry)
A reverse phase HPLC method is described for the determination of cinitapride hydrogen tartrate in the presence of its degradation products in bulk drug. A drug was subjected to all stress conditions such as reduction, oxidation acidic and alkaline medium. Chromatography was recorded on an Intersil ODS-3 column using mixture of acetonitrile and phosphate buffer, pH adjusted to 6.7 in the ratio (70:30 v/v) as the mobile phase at the rate of 1.0 mL/min with detection at 260 nm. Glimepride was used as internal standard. The retention time of drug cinitapride was 3.8 min and glimepride an internal standard was 2.5 minute. The drug was found to degrade extensively in reduction conditions and mild degradation in the presence of in alkaline, acidic and oxidative but the drug was stable in thermal stress. The method was validated by determining its specificity, linearity, precision and accuracy. The developed method with good separation of all degradation products from drug could be successfully applied for the determination of cinitapride in the presence of its degradation products in the bulk drug. The proposed method is simple, fast, accurate and precise and hence applied for routine quality control of cinitapride in bulk drug. It can be used for analysis of samples during stability testing.